Diosgenin Loaded Polymeric Nanoparticles with Potential Anticancer Efficacy - Nikita Sharma; Monisha Singhal; R. Mankamna Kumari; Nidhi Gupta; Romila Manchanda; Asad Syed; Ali H. Bahkali; Surendra Nimesh (Biomolecules, 2020)
This study aims to determine the anticancer efficacy of diosgenin encapsulated poly-glycerol malate co-dodecanedioate (PGMD) nanoparticles. Diosgenin loaded PGMD nanoparticles (variants 7:3 and 6:4) were synthesized by the nanoprecipitation method. The synthesis of PGMD nanoparticles was systematically optimized employing the Box-Behnken design and taking into account the influence of various independent variables such as concentrations of each PGMD, diosgenin and PF-68 on the responses such as size and PDI of the particles. Mathematical modeling was done using the Quadratic second order modeling method and response surface analysis was undertaken to elucidate the factor-response relationship. The obtained size of PGMD 7:3 and PGMD 6:4 nanoparticles were 133.6 nm and 121.4 nm, respectively, as measured through dynamic light scattering (DLS). The entrapment efficiency was in the range of 77–83%. The in vitro drug release studies showed diffusion and dissolution controlled drug release pattern following Korsmeyer–Peppas kinetic model. Furthermore, in vitro morphological and cytotoxic studies were performed to evaluate the toxicity of synthesized drug loaded nanoparticles in model cell lines. The IC50 after 48 h was observed to be 27.14 µM, 15.15 µM and 13.91 µM for free diosgenin, PGMD 7:3 and PGMD 6:4 nanoparticles, respectively, when administered in A549 lung carcinoma cell lines.